EFEKTIVITAS PENERAPAN FLIPPED CLASSROM DAN EXO OLO TASK PADA POSISI STRATEGIS INDONESIA SEBAGAI POROS MARITIM DUNIA DI SMA NEGERI 8 PADANG - Aftriana Hadi; Nofrion Nofrion (JURNAL BUANA, 2021)
The purpose of this study was to determine the effectiveness of the aspects of learning activities and student learning outcomes. The method used in this research is Quasi Experimental with a design using a control group without a pretest. The study population was all students of class XI IPS at SMA Negeri 8 Padang, totaling 141 students. Samples were selected randomly. The class chosen to be the control class was class XI IPS 2 and the experimental class was XI IPS 1 at SMA Negeri 8 Padang. In this study, the following results were found. 1) the EXO OLO Task-based Flipped Classroom learning method which is applied to geography learning, especially the material of Indonesia's Strategic Position as a World Maritime Axis in the experimental class is proven to have a significant difference in value with the control class which is not given special behavior based on the results of different tests using the t-test. the value of tcount = 4.302 with a significant level of 5% then the value of t table = t (0.05 / 2, 61) = 1.9992 so it can be concluded that the value of tcount> ttable, so Ho is rejected. 2) In this study, both the control class and the experimental class were dominated by working on the questions independently. 3) The learning resources used by students are dominated by the internet, by accessing them via smartphones. 4) The quality of the network that influences the learning process does not change from the first meeting to the third meeting in both the control and experimental classes, with the highest percentage of network quality in the control class which is stable and the experimental class is dominated by less stable.